-3x-3+9x+7x-x=29

Simple and best practice solution for -3x-3+9x+7x-x=29 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3x-3+9x+7x-x=29 equation:


Simplifying
-3x + -3 + 9x + 7x + -1x = 29

Reorder the terms:
-3 + -3x + 9x + 7x + -1x = 29

Combine like terms: -3x + 9x = 6x
-3 + 6x + 7x + -1x = 29

Combine like terms: 6x + 7x = 13x
-3 + 13x + -1x = 29

Combine like terms: 13x + -1x = 12x
-3 + 12x = 29

Solving
-3 + 12x = 29

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '3' to each side of the equation.
-3 + 3 + 12x = 29 + 3

Combine like terms: -3 + 3 = 0
0 + 12x = 29 + 3
12x = 29 + 3

Combine like terms: 29 + 3 = 32
12x = 32

Divide each side by '12'.
x = 2.666666667

Simplifying
x = 2.666666667

See similar equations:

| (6x-w)(7x+w)= | | 14z+11-5z= | | 2+(-9)=f-4 | | 2mp+3np+2mr+3nr= | | 3n-4+6n+2=6+4n+2 | | (-5)-(-8)=g+7 | | 4x+4=19-x | | (-37)=c+(-14) | | 6a-2-4a=3a+4+5a | | 0=-5n-2n-2n | | (-5)=b+(-11) | | -8x^2-8x+160=0 | | A-5=(-8) | | 3x*26= | | 6(x-1)+2=6x-2 | | -7y=-10-8y | | 0=-4.9t^2+.686t | | J+(-3)=4 | | 7j+4=5j | | -5x-15=-20 | | 9y=9+10y | | -12+8+5=36 | | 2x+34x^2-322=0 | | 3+(-7)=f-3 | | 3y+9-8y+6-6=-5y-12 | | -12+3x=-6 | | 9n=-117 | | 3x+9-8x+6-6=-5x-12 | | 3+(-7)=4 | | -0.9+z=0.075 | | 69=3u | | 0.06x+0.02(7-x)= |

Equations solver categories